2009
DOI: 10.2527/jas.2008-1005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of level and duration of dietary n-3 polyunsaturated fatty acid supplementation on the transcriptional regulation of Δ9-desaturase in muscle of beef cattle1

Abstract: The objective of this study was to examine the effect of level and duration of feeding of an n-3 PUFA-enriched fish oil (FO) supplement in combination with soybean oil (SO) on the transcriptional regulation of Delta(9)-desaturase gene expression in bovine muscle. Beef bulls (n = 40) were assigned to 1 of 4 iso-lipid and isonitrogenous concentrate diets fed for ad libitum intake for a 100-d finishing period. Concentrates were supplemented with one of the following: 1) 6% SO (CON); 2) 6% SO + 1% FO (FO1); 3) 6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
70
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 32 publications
17
70
2
4
Order By: Relevance
“…It might be possible that the tissuespecific effect of n-3 PUFA-supplemented diet on D6d protein expression in our experiments is related to tissue-specific distribution/regulation of the relevant transcription factors. This suggestion is supported by data of the literature that n-3 PUFAenriched diet inhibits SREBP-1c in muscle tissue of bulls (Waters et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It might be possible that the tissuespecific effect of n-3 PUFA-supplemented diet on D6d protein expression in our experiments is related to tissue-specific distribution/regulation of the relevant transcription factors. This suggestion is supported by data of the literature that n-3 PUFAenriched diet inhibits SREBP-1c in muscle tissue of bulls (Waters et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…One possible reason could be dietary modulation of the rate of n-3 and n-6 fatty acids transfer into the tissues. Waters et al (2009) described that the balance between n-6 and n-3 PUFA in the diet is important for the regulation of SCD through SREBP-1c in muscle of beef cattle. However, this explanation could be applied to C18:2n-6 and C18:3n-3 fatty acids, but not to longer-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The strategic supplementation of cattle diets can generate beef with increased conjugated linoleic acid (CLA) and n-3 -E-mail: Sinead.Waters@teagasc.ie polyunsaturated fatty acid (PUFA) concentrations, a lower quantity of fat and a fatty acid profile more compatible with current human dietary recommendations (Moloney et al, 2001). More recently, however, it has been shown that the simultaneous accretion of tissue concentrations of n-3 PUFA and CLA appears to be hampered by the apparent negative effects of n-3 PUFA on tissue CLA synthesis (Waters et al, 2009). Our group has shown that increases in dietary n-3 PUFA supplementation decreased mRNA levels for D-9 desaturase in muscle (Waters et al, 2009).…”
Section: Introductionmentioning
confidence: 80%
“…0 (control), 50 or 100 mM, n 5 16 (8 for fatty acid analysis and 8 for gene expression analysis) for each treatment. The EPA concentrations selected were based on in vivo EPA concentrations recorded in bovine muscle tissue as part of an in vivo experiment at our laboratory (Waters et al, 2009). Following the 24 h incubation, cells and media were harvested.…”
Section: Rna Isolationmentioning
confidence: 99%
See 1 more Smart Citation